A missing piece of pancreas: A rare case report of dorsal pancreatic agenesis presenting as acute pancreatitis (Indian Journal of Case Reports, 2026)
There are various congenital anomalies of the pancreas, among which dorsal pancreatic agenesis is a very rare entity <120 cases reported till now. It is due to absent dorsal bud derivatives. It can be asymptomatic or can present as abdominal pain, pancreatitis, and hyperglycemia. A 42-year-old gentleman presented with sudden onset abdominal pain and, on evaluation, was diagnosed to have acute pancreatitis. Incidentally noted to have dorsal pancreatic agenesis, a congenital anomaly which presented as acute pancreatitis. He was managed with hydration, multimodal analgesia, and nutrition. Complications associated with it must be kept in mind, such as pancreatitis and diabetes/hyperglycemia secondary to insulin deficiency. Early diagnosis and prompt treatment of complications of dorsal pancreatic agenesis is the key.